Antecedents of Flood Victims Psychological Well-Being: A Quantitative Analysis - Mustaffa, Che Su; Zakaria, Nurlela (International Review of Management and Marketing, 2016)
The purpose of this paper is to examine the relationship between perceived source credibility and impression management with psychological well-being among people in flood prone areas. This paper is based on quantitative approach by conducting a survey to 386 people in flood prone areas in Kubang Pasu district, Kedah, Malaysia. Few literatures on source credibility, impression management and psychological well-being that constitute the building blocks of this model have discussed. This paper also discusses the findings of the relationships between these variables by fill in the gap identified from previous studies by applying it in a new context of flood disaster management. On the other hand, the findings provide support for the relationships between perceived source credibility and impression management with psychological well-being among people flood prone areas. Keywords: Source Credibility, Impression Management, Psychological Well-being JEL Classifications: I31, D83, D81, Q54